2001
DOI: 10.1002/dys.199
|View full text |Cite
|
Sign up to set email alerts
|

Word recognition deficits in German: more evidence from a representative sample

Abstract: In a representative sample of German speaking dyslexic children, earlier findings on dyslexia in the highly consistent orthography of German were confirmed. In a sample of 78 dyslexic 3rd graders selected on the basis of their poor word recognition skills, reading accuracy for both words and non-words was deficient but high in absolute terms. This indicates that the highly consistent grapheme-phoneme correspondences of German orthography in combination with the straightforward phonics teaching approach, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
68
0
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 15 publications
11
68
0
7
Order By: Relevance
“…1; While in terms of reading, Spanish is a highly regular language, some specific phonemes can be represented by different graphemes when written. As reported by Landerl (2001) for German, orthographical knowledge in SN seems to be very limited and a deficit in writing is a typical feature of dyslexia in German. Something similar is found in Spanish, at least for slow-naming children, who showed significantly greater difficulty in recognizing orthographic violations, as well as more marked reading-writing acquisition problems compared to AN children.…”
Section: Behavioral Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…1; While in terms of reading, Spanish is a highly regular language, some specific phonemes can be represented by different graphemes when written. As reported by Landerl (2001) for German, orthographical knowledge in SN seems to be very limited and a deficit in writing is a typical feature of dyslexia in German. Something similar is found in Spanish, at least for slow-naming children, who showed significantly greater difficulty in recognizing orthographic violations, as well as more marked reading-writing acquisition problems compared to AN children.…”
Section: Behavioral Resultsmentioning
confidence: 72%
“…The highly consistent grapheme-phoneme correspondences of these orthographies, together with the straightforward phonics-based teaching approach, allow even dyslexic children to acquire the process of phonological decoding (Landerl & Wimmer, 2008;Seymour, Aro, & Erskine, 2003;Landerl, 2001). The different potential solutions to the mapping problem suggest that children will develop distinct reading strategies in response to differences in orthographic structure across orthographies; distinct strategies that might underlie differences in the dyslexic symptoms observed in children who acquire reading skills in shallow or deep orthographic systems.…”
Section: Introductionmentioning
confidence: 99%
“…24 In languages such as German, Italian and Finnish, with a more regular orthography than English, low reading speed, rather than accuracy of reading, is a prominent and persistent problem for dyslexics. [84][85][86][87][88] It has also been suggested that processing speed decreases more with aging in dyslexics as compared to nondyslexic individuals. 88 Therefore, in these countries, speed or automaticity of reading appears to be the seminal deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Following Bowers and Wolf's (1993) hypothesis that naming speed is a significant predictor of reading fluency in English-speaking children quite independently of phonological processing, there has been considerable interest in its role as a predictor of variation in reading abilities among children learning to read in transparent languages including Finnish (Korhonen, 1995), Spanish (Escribano, 2007;Jiménez et al, 2008;Novoa & Wolf, 1984), German (Frith et al, 1998;Landerl, 2001;Wimmer, Mayringer & Landerl, 2000), Italian (Di Filippo et al, 2005), and Dutch (van den Bos, 1998;Yap & van der Leij, 1993). Taken together, these studies' findings are broadly consistent with the view that rapid naming problems seem to be one of the main characteristics of dyslexic children learning to read in a transparent orthography.…”
Section: Naming Speed Deficits Across Different Languagesmentioning
confidence: 99%